2000
DOI: 10.1038/eye.2000.189
|View full text |Cite
|
Sign up to set email alerts
|

Pigmented paravenous retinochoroidal atrophy: A literature review supported by a unique case and insight

Abstract: Pigmented paravenous retinochoroidal atrophy (PPRCA) is a rare disorder of unknown origin characterised by bone corpuscle pigmentation accumulation along the distribution of the retinal veins. In

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 19 publications
1
19
0
2
Order By: Relevance
“…The earliest case report indicated an inflammatory cause since the affected individual had tubercular spondylitis (1), while another early case report described a child with congenital syphilis (32). Following these early studies, a number of inflammatory PPRCA cases were reported with a variety of inflammatory causes, including Behçet’s disease (33), measles (34), rubeola (35), uveitis (11,36) and other unknown causes of inflammation (4,37). However, these cases that developed due to various inflammatory agents or other definite reasons, particularly inflammatory retinal vein vasculopathy resulting from various causes, are not real PPRCA but should be considered as a pseudo PPRCA.…”
Section: History and General Backgroundmentioning
confidence: 99%
See 4 more Smart Citations
“…The earliest case report indicated an inflammatory cause since the affected individual had tubercular spondylitis (1), while another early case report described a child with congenital syphilis (32). Following these early studies, a number of inflammatory PPRCA cases were reported with a variety of inflammatory causes, including Behçet’s disease (33), measles (34), rubeola (35), uveitis (11,36) and other unknown causes of inflammation (4,37). However, these cases that developed due to various inflammatory agents or other definite reasons, particularly inflammatory retinal vein vasculopathy resulting from various causes, are not real PPRCA but should be considered as a pseudo PPRCA.…”
Section: History and General Backgroundmentioning
confidence: 99%
“…Certain patients who complained of poor dark adaptation, poor night vision or a blind eye did not suffer from PPRCA but instead had retinitis pigmentosa (RP) or pseudo PPRCA, as aforementioned (4,19,20,26,30,37). Particular observations in PPRCA have also been reported, including a shadow in front of the eye, diminished peripheral vision, mild pain and photopsia, involuntary closure of the upper eyelid, headaches and observing halos around lights (4,15,39). However, whether these observations are associated with the disease entity remains unknown.…”
Section: Clinical Featuresmentioning
confidence: 99%
See 3 more Smart Citations